Current Predictors of Atrial Fibrillation Progression - V. I. Podzolkov; A. I. Tarzimanova (Рациональная фармакотерапия в кардиологии)
Aim. To identify predictors of progression of atrial fibrillation (AF) in patients with hypertension (HT), coronary heart disease (CHD) and chronic heart failure (CHF) with recurrent AF.Material and methods. The study included 31 2 patients with recurrent AF. The patients were divided into 3 groups according to a leading underlying condition: essential HT (n=1 36), CHD (n=11 2), and CHF with III-IV functional class by NYHA (n=64). The average follow-up duration was 60±3 months. Progression of AF was defined as development of long-standing persistent or permanent AF.Results. All three groups of patients with recurrent AF revealed progression of the arrhythmia from paroxysmal or persistent to a sustained permanent form during the 5-year prospective follow-up. The rate of AF progression in the patients with CHF was significantly higher and accounted for 59% as compared to 46% in the patients with hypertension (p=0.002) and 51% in the patients with CHD (p=0.008). AF progression in patients with HT correlated significantly with left ventricular (LV) hypertrophy (odds ratio [OR] 1.25; 95% confidence interval [95%CI] 1.03-1.52) and increased arterial wall stiffness (OR 2.3; 95%CI 1.95-2.65). The independent predictors of arrhythmia progression in patients with CHD were a history of myocardial infarction (OR 1.23; 95%CI 0.9-1.5), irreversible LV wall motion abnormalities (OR 1.41; 95%CI 1.1-1.7), and increased plasma level of N-terminal pro-A-type natriuretic peptide (Nt-proANP; OR 1.16; 95%CI 0.8-1.4). Reduction in LV ejection fraction below 40% (OR 0.84; 95%CI 0.7-0.89) and increased plasma N-terminal pro-B-type natriuretic peptide (Nt-proBNP; OR 2.3; 95%CI 1.93-2.67) were independent predictors of AF progression from persistent to permanent form in the patients with systolic heart failure.Conclusion. Progression of AF is related to the underlying cardiovascular disease. The early vascular aging syndrome and LV hypertrophy are the main factors of AF progression in patients with HT. Previous myocardial infarction with irreversible hypokinesia is associated with AF progression in patients with CHD. Reduced LV ejection fraction and increased plasma BNP predict AF progression in patients with CHF.